Triclinic wollastonite type nickel-based catalyst for hydrogen production by autothermal reforming of acetic acid
The trisilica wollastonite-type nickel-based catalyst prepared by hydrothermal method solves the problems of poor catalyst stability and carbon accumulation in the acetic acid autothermal reforming reaction, and achieves efficient acetic acid conversion and stability of hydrogen yield.
Patent Information
- Application Number
- CN202510060839.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-08
AI Technical Summary
In the existing acetic acid autothermal reforming reaction, there are problems such as poor stability, easy carbon accumulation of active components, oxidation and sintering, resulting in reduced catalyst activity or even inactivation.
The CaSiO3 trisilite-type nickel-based catalyst with Ni as the active component was prepared by hydrothermal method. By introducing the trisilite structure as a support, the dispersion and thermal stability of the active site were enhanced, and sintering and carbon accumulation were inhibited.
The activity, stability and anti-carbon deposit properties of the catalyst are improved. It is preferred that the acetic acid conversion rate of the catalyst is close to 100%, the hydrogen yield is stable, and it has excellent characteristics of anti-oxidation, anti-sintering and anti-carbon deposits.
Smart Images

Figure CN119771416A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a triclinic wollastonite nickel-based catalyst for producing hydrogen through autothermal reforming of acetic acid, belonging to the field of producing hydrogen through autothermal reforming of acetic acid. Background Art
[0002] Hydrogen is a clean energy carrier that can be obtained through water electrolysis, biomass conversion and other methods. Among them, biomass hydrogen production uses renewable biomass resources and is a promising way to obtain green hydrogen. However, the yield of direct hydrogen production from biomass is low; biomass oil is obtained through rapid thermal cracking of biomass, and biomass oil is mainly composed of acetic acid, etc. Therefore, acetic acid derived from biomass can be used as a good raw material for hydrogen production.
[0003] Acetic acid can be used to produce hydrogen through the reforming process. The traditional acetic acid steam reforming reaction is an endothermic reaction, and heat transfer often restricts the dynamic and rapid regulation of hydrogen production. The partial oxidation reaction introduces oxygen and acetic acid as raw materials, which is an exothermic reaction. However, the strong oxidizing property will make the catalyst easy to sinter and deactivate, and the hydrogen production rate is low. The acetic acid autothermal reforming hydrogen production reaction (CH3COOH+aO2+bH2O→cCO+dCO2+eH2, ΔH=0 kJ / mol) combines the above two methods of preparing hydrogen. By controlling the ratio of oxygen to reactants and balancing the heat supply of the reaction system, self-heating is achieved, which has significant advantages.
[0004] In the process of preparing hydrogen by autothermal reforming of acetic acid, nickel-based catalysts have high activity in cracking CC, CO and CH bonds. However, in the autothermal reforming atmosphere containing oxygen, the active components of the nickel-based catalyst will be deactivated due to oxidation, and the high temperature of autothermal reforming will cause catalyst sintering; at the same time, in the autothermal reforming process, carbon-containing products such as CO, CO2, C2H4, and CH2CO will be produced during the acetic acid reforming reaction, water gas conversion, and acetic acid thermal cracking reaction. These products may further undergo methanation or polymerization reactions to form carbon deposits covering the active components, resulting in reduced catalyst activity or even inactivation.
[0005] Therefore, in order to address the sintering, oxidation and carbon deposition problems of the above nickel-based catalysts in the autothermal reforming process of acetic acid, the present invention adopts a hydrothermal method to create a CaSiO3 triclinic wollastonite nickel-based catalyst with Ni as the active component, which is applied to the autothermal reforming process of acetic acid to produce hydrogen, and has the following creativity.
[0006] First, in the catalyst of the present invention, the constructed carrier CaSiO3 is a triclinic metasilicate belonging to the P1 space group, which is composed of silicon-oxygen tetrahedrons and silicon-oxygen isolated tetrahedrons alternately connected, and calcium octahedrons are interspersed between these chains, and the entire structure is stabilized by sharing oxygen atoms with the tetrahedrons, providing a stable reaction interface for the conversion of acetic acid and inhibiting the sintering of the active component Ni; secondly, triclinic wollastonite CaSiO3 is used as a carrier of Ni, and a strong interaction is formed between the nickel species and the carrier, which enhances the dispersibility and thermal stability of the Ni active sites and improves the activity, stability and anti-coking performance of the catalyst; in addition, in the constructed triclinic wollastonite structure, the Ca species, as an alkaline earth metal, improves the overall alkalinity of the catalyst, helps to adsorb and activate water molecules, form intermediate species such as OH* and O*, and react with CH x *(x=0-3) and other carbon-containing species react to promote the elimination of carbon deposits on the catalyst surface, thereby improving the anti-carbon deposition ability of the nickel-based catalyst; finally, the calcium-silicon triclinic wollastonite nickel-based catalyst prepared by the hydrothermal method of the present invention is a mesoporous material, and its porous structure is beneficial to the diffusion and transfer of product molecules and reactant molecules, which is beneficial to improving the dispersion of Ni, improving the activity of the catalyst, inhibiting the polymerization of ethylene ketone, a carbon deposit precursor in hydrogen production by autothermal reforming of acetic acid, and reducing the formation of carbon deposits.
[0007] The innovation of the present invention in the catalyst composition and structure enables the catalyst to exhibit good activity, stability, and resistance to oxidation, sintering and carbon deposition in the acetic acid autothermal reforming reaction, and improves the conversion rate of acetic acid and the selectivity of hydrogen, showing the characteristics of an excellent catalyst. Summary of the invention
[0008] The technical problem to be solved by the present invention is to provide a new catalyst with stable structure, high conversion rate, good selectivity, resistance to oxidation, resistance to sintering and resistance to carbon deposition, in view of the problems of poor stability of the catalyst in the existing acetic acid autothermal reforming reaction, easy carbon deposition of active components, reduced catalyst activity or even deactivation due to oxidation and sintering.
[0009] The present invention uses Ni as an active component, introduces a CaSiO3 triclinic wollastonite structure as a carrier, and adopts a hydrothermal method to prepare a nickel-based catalyst. The catalyst of the present invention is used in the autothermal reforming of acetic acid to produce hydrogen. When the reaction temperature is 650 ° C, the conversion rate of acetic acid of the preferred catalyst is close to 100%, and the hydrogen yield is stable at about 2.74 mol-H2 / mol-HAc.
[0010] Technical solution of the present invention:
[0011] The present invention is based on the characteristics of acetic acid autothermal reforming and uses a hydrothermal method to prepare a Ni / CaSiO3 catalyst. The molar composition of the catalyst of the present invention is (NiO) a (CaO)b (SiO2) c , wherein a is 0.75-0.86, b is 2.67-3.25, and c is 2.69-3.23; the composition in terms of weight percentage of oxides is: nickel oxide is 14.0%-16.0%, calcium oxide is 37.5%-45.5%, silicon oxide is 40.4%-48.5%, and the sum of the weight percentages of each component is 100%.
[0012] The specific preparation method steps are as follows:
[0013] 1) Prepare a mixed solution of metal nitrates: weigh a certain amount of calcium nitrate tetrahydrate and sodium silicate nonahydrate according to a certain molar ratio, add deionized water, and stir to form a suspension 1#;
[0014] 2) Preparation of precipitant: According to the molar ratio [OH - ] / [Ca 2+ +Si 4+ ]=8, [OH - ] / [CO3 2- ]=16, weigh Na2CO3 and NaOH to prepare a precipitant, and dissolve them in deionized water to form a mixed solution 2#;
[0015] 3) Under the conditions of pH=10.5±0.5 and 60-75 °C, slowly drop suspension 1# and solution 2# to carry out precipitation reaction, then add hexadecyltrimethylammonium bromide, stir for 2 hours, transfer to a reactor, and place in a drying oven at 150 °C for 36 hours; filter, wash and dry the suspension in the reactor, heat the obtained precursor to 850 °C at a rate of 5 °C / min and calcine at this temperature for 4 hours to obtain a triclinic wollastonite CaSiO3 carrier;
[0016] 5) A certain amount of Ni(NO3)2·6H2O was dissolved in deionized water, and a triclinic wollastonite CaSiO3 carrier was added. After being immersed in a water bath at 80°C for 12 hours, the mixture was dried at 105°C for 12 hours, heated to 500°C at a heating rate of 10°C / min and maintained for 4 hours, and then reduced in H2 at 600-800°C for 1 hour to obtain a Ni / CaSiO3 catalyst in which the metallic nickel phase was supported on the wollastonite structure, forming a Ni-Ca-Si-O x The active center has a typical structure such as Figure 1 shown.
[0017] Beneficial effects of the present invention:
[0018] 1) The catalyst of the present invention uses Ni as an active component, introduces triclinic wollastonite CaSiO3 as a carrier by a hydrothermal preparation method, forms a stable Ni / CaSiO3 structure, and obtains Ni-Ca-Si-O x Active center. The catalyst of the present invention exhibits good selectivity, catalytic activity and oxidation resistance in the catalysis of hydrogen production by autothermal reforming of acetic acid, and the acetic acid conversion rate of the preferred catalyst is about 100%, and the hydrogen yield is stable at about 2.74 mol-H2 / mol-HAc.
[0019] 2) The triclinic wollastonite nickel-based catalyst prepared by the hydrothermal synthesis method of the present invention has the following characteristics:
[0020] ① The carrier CaSiO3 wollastonite used in the catalyst construction of the present invention is a triclinic calcium metasilicate mineral with good heat resistance and chemical stability. Its Pearson structure symbol is aP30 and its space group is P1. Its structure is composed of single chains with no specific length, which run along the b axis and have a triple periodicity. These chains are composed of double silicon tetrahedrons [Si2O7] 6- and single silicon tetrahedron [SiO4] 4- The CaSiO3 crystal is composed of two pairs, and the calcium ions are located in the distorted silicon-oxygen polyhedron with low symmetry, which makes oxygen defect vacancies appear in the CaSiO3 crystal; among them, there are three inequivalent calcium (Ca) sites, whose Ca-O bond lengths range from 2.27 to 2.61Å, and the calcium atoms are bonded to the oxygen atoms in seven-coordinate, six-coordinate and distorted six-coordinate geometric structures; at the same time, there are three inequivalent silicon sites, whose Si-O bond lengths range from 1.59 to 1.67Å, and silicon is bonded to four oxygen atoms to form silicon-oxygen tetrahedra, which share corners and edges with the calcium-oxygen octahedron and silicon-oxygen tetrahedron, and are tilted. Angle 43-63°; in addition, there are nine unequal oxygen sites, and the oxygen atoms are bonded to calcium and silicon atoms in three-coordinate, 150° twisted bend, four-coordinate, twisted triangular plane and twisted rectangular swinging geometric structures; these local lattice distortions and multi-coordinate structures constructed by the present invention are conducive to the formation of more oxygen defect vacancies, effectively promoting the migration of oxygen ions in the lattice, promoting the adsorption, activation and decomposition of CH3COOH, H2O and O2 in the reaction gas and the conversion of the generated carbon-containing intermediates (CH3COO*, CH3CO*, CH3*, etc.), and improving the carbon deposition precursor CH x The gasification ability of * / C* effectively inhibits the formation of by-products such as acetone and improves the catalyst's anti-coking performance.
[0021] ② In the triclinic wollastonite Ni / CaSiO3 structure constructed by the present invention, Ca 2+ and Si 4+The strong ionic characteristics of the interaction between them have excellent thermal stability, which not only provides a stable reaction interface for the conversion of acetic acid, but also enhances the interaction between the active component Ni and the carrier CaSiO3, thereby effectively inhibiting the possible migration, aggregation and sintering of the active component under high temperature reaction conditions.
[0022] ③ In the triclinic wollastonite structure constructed by the present invention, silicon and oxygen form a Si-O bond with high bond energy (452 kJ / mol), which has a strong ionic property, is conducive to the loss of surface oxygen, and promotes the formation of oxygen vacancies and the diffusion of oxygen ions; and, alkaline earth metal calcium (Ca) has a high electropositivity, while oxygen (O) has a high electronegativity. This electronegativity difference leads to electron transfer in the Ca-O bond, making the oxygen ions in the Ca-O bond highly transferable and active, and the large amount of active oxygen ions formed promotes the formation of CH4+ in the process of acetic acid conversion. x The gasification of intermediate species such as *(x=0-3) further improves the catalyst's ability to resist carbon deposition.
[0023] 3) The present invention adopts a hydrothermal synthesis method to prepare a triclinic wollastonite nickel-based catalyst with a mesoporous structure, and uses hexadecyltrimethylammonium bromide as a template to construct a typical porous structure, which effectively increases the specific surface area of the carrier, thereby improving the dispersion of the active components, increasing the number of catalytic active centers on the surface, and effectively improving the activity of the catalyst.
[0024] 4) The results of the acetic acid autothermal reforming reaction show that the catalyst of the present invention can efficiently convert acetic acid and has a high hydrogen yield during the acetic acid conversion process, and can effectively inhibit the generation of by-products. It has excellent properties such as stability, anti-oxidation, anti-sintering, and anti-carbon deposition. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 : X-ray diffraction spectrum of a typical catalyst of the present invention after reduction;
[0026] Figure 2 : BJH pore size distribution diagram of a typical catalyst of the present invention. DETAILED DESCRIPTION
[0027] Reference example one
[0028] 24.99g of Al(NO3)3·9H2O and 2.33g of Ni(NO3)2·6H2O were weighed into a beaker, and a certain amount of deionized water was added to dissolve to obtain solution 1#; then 8.34g of sodium hydroxide and 1.38g of anhydrous sodium carbonate were weighed, and a certain amount of deionized water was added to dissolve to obtain solution 2#; at 65°C and pH=10.5±0.5, solution 1# and solution 2# were slowly added dropwise for coprecipitation reaction, and the temperature was maintained for stirring and aging for 24 hours; the precipitate was obtained after 3 times of suction filtration and washing, and then transferred to a 105°C oven for drying for 24 hours to obtain a precursor; the temperature was increased to 700°C in a tubular furnace at a heating rate of 10°C / min and maintained for 4 hours to obtain a CDUT-NA catalyst, forming a Ni-based catalyst supported on Al2O3; the weight percentage composition of the catalyst in terms of oxides is: 15.1% nickel oxide and 84.9% aluminum oxide.
[0029] The activity evaluation of acetic acid autothermal reforming reaction was carried out in a continuous flow fixed bed reactor. The catalyst was ground and tableted, then sieved into 20-40 mesh particles, 0.2 g was weighed and loaded into the reactor, and reduced in H2 at a temperature of 600-800°C for 1 hour; then the mixed solution of acetic acid and water was injected into the vaporizer by a constant flow pump for vaporization, mixed with oxygen, and nitrogen was used as the internal standard gas to form a reaction raw gas with a molar composition of CH3COOH / H2O / O2 / N2=1 / (1.3-5.0) / (0.21-0.35) / (2.5-4.5), and this raw gas was introduced into the reaction bed. The reaction conditions were 600-800°C, normal pressure, and a space velocity of 10000-35000mL / (g catalyst h), the reaction tail gas was analyzed online by gas chromatography.
[0030] The catalyst CDUT-NA was tested for its activity in the autothermal reforming of acetic acid under the conditions of normal pressure and space velocity of 25000 mL / (g catalyst ·h), reaction temperature is 700 ° C, raw gas acetic acid / water / oxygen = 1 / 4.0 / 0.28, in the 10-hour activity experiment, the conversion rate of acetic acid gradually decreased from 93.5% to 64.6%, and the hydrogen yield also gradually decreased from 2.27mol-H2 / mol-HAc to 0.78mol-H2 / mol-HAc; the low hydrogen yield is not only due to the low conversion rate of acetic acid, but also because the by-product selectivity is extremely high, and the selectivity of the by-product acetone increases to about 41.2%, indicating that the acetic acid ketonization reaction mainly occurred during the experiment. XRD, BET and other characterization results show that the catalyst has poor stability in the process of acetic acid autothermal reforming, and there are many by-products. The acetonization reaction is not effectively suppressed, sintering, carbon deposition and partial oxidation occur, and the activity is low.
[0031] Embodiment 1
[0032] Weigh 8.32 g of Na2SiO3·9H2O and 6.91 g of Ca(NO3)2·4H2O in a beaker, add a certain amount of deionized water, stir and mix to obtain suspension 1#; then weigh 12.78 g of sodium hydroxide and 2.11 g of anhydrous sodium carbonate, dissolve in deionized water to form mixed solution 2#; at 65°C and pH 10.5±0.5, slowly drop suspension 1# and solution 2# to perform precipitation reaction; then add 0.5 g of hexadecyltrimethylammonium bromide to the obtained suspension, stir for 2 hours, transfer to a reactor, and place in an oven at 150°C for 36 hours; filter, wash and dry the suspension in the reactor, and heat the obtained precursor to 850°C at a heating rate of 5°C / min. °C and kept for 4 hours to obtain a triclinic wollastonite CaSiO3 carrier; then, 2.33g of Ni(NO3)2·6H2O was dissolved in deionized water, 3.40g of the CaSiO3 carrier was added, and the mixture was immersed for 12 hours, stirred and evaporated in a water bath at 80 °C, dried at 105 °C for 12 hours, and heated to 500 °C at a heating rate of 10 °C / min and kept for 4 hours; after being reduced by hydrogen at 700 °C, the crystal structure was as shown in the attached figure. Figure 1 As shown in the figure, a CaSiO3 peak with a triclinic wollastonite structure and a diffraction peak of metallic nickel are formed, and a Ni-Ca-Si-O x The Ni / CaSiO3 catalyst with active centers is CDUT-NCS catalyst, which has the following weight percentages of oxides: 15.0% nickel oxide, 41.0% calcium oxide, and 44.0% silicon oxide.
[0033] The catalyst CDUT-NCS was tested for its activity in autothermal reforming of acetic acid under normal pressure and space velocity of 25000 mL / (g catalyst ·h), reaction temperature is 650°C, raw gas acetic acid / water / oxygen = 1 / 4.0 / 0.28, the conversion rate of acetic acid is close to 100%, the hydrogen yield is stable at about 2.74mol-H2 / mol-HAc, the selectivity of CO2 is about 68.2%, the selectivity of CO is about 30.7%, only a small amount of by-products are produced, the catalyst activity remains stable, and no deactivation is observed. The CDUT-NCS catalyst was characterized by low-temperature nitrogen physical adsorption, as shown in the attached Figure 2 As shown, the specific surface area is 30.3m 2 / g, pore volume 0.1cm 3 / g, with an average pore size of 17.7nm, which is a mesoporous material. The results show that the catalyst has good stability in the process of acetic acid autothermal reforming, and the CaSiO3 carrier still exists stably before and after the reaction, providing a stable reaction site for the catalyst.
Claims
1. Application of Ni / CaSiO3 catalyst supported on triclinic wollastonite structure in hydrogen production from acetic acid autothermal reforming, characterized in that: 0.1-0.2g of catalyst was weighed and reduced in H2 at a temperature of 600-800°C for 1 hour, purged with nitrogen, and then the mixed solution of acetic acid and water was injected into a vaporizer by a constant flow pump for vaporization, mixed with oxygen, and nitrogen was used as an internal standard gas to form a reaction raw gas with a molar composition of CH3COOH / H2O / O2 / N2=1 / (1.3-5.0) / (0.21-0.35) / (2.5-4.5), and the raw gas was introduced into the reaction bed. The reaction conditions were 600-800°C, normal pressure, and a space velocity of 10000-35000mL / (g catalyst ·h); the catalyst is prepared by the following method: weigh a certain amount of sodium silicate nonahydrate and calcium nitrate tetrahydrate, add deionized water, stir and mix to form a suspension 1#; weigh a certain amount of sodium carbonate and sodium hydroxide, dissolve in deionized water to form a mixed solution 2#; under the conditions of pH=10.5±0.5 and 60-75°C, slowly dropwise add the suspension 1# and solution 2# to perform a precipitation reaction; then add hexadecyltrimethylammonium bromide, stir for 2 hours, transfer to a reactor, and place in an oven at 150°C for 36 hours; After filtering, washing and drying the suspension, the obtained precursor was heated to 850°C at a heating rate of 5°C / min and maintained for 4 hours to obtain a triclinic wollastonite CaSiO3 carrier; then, a certain amount of nickel nitrate hexahydrate was dissolved in deionized water, added to the CaSiO3 carrier, immersed in a water bath at 80°C for 12 hours, dried at 105°C for 12 hours, and heated to 500°C at a heating rate of 10°C / min and maintained for 4 hours; after being reduced by hydrogen at 600-800°C, Ni-Ca-Si-O x Active center, obtain Ni / CaSiO3 catalyst in which metal nickel is supported on triclinic wollastonite structure; the molar composition of the catalyst of the present invention in terms of oxide is (NiO) a (CaO) b (SiO2) c , wherein a is 0.75-0.86, b is 2.67-3.25, and c is 2.69-3.23; the composition in terms of weight percentage of oxides is: nickel oxide is 14.0%-16.0%, calcium oxide is 37.5%-45.5%, silicon oxide is 40.4%-48.5%, and the sum of the weight percentages of each component is 100%.
2. Application of the Ni / CaSiO3 catalyst supported on a triclinic wollastonite structure according to claim 1 in a process of producing hydrogen from acetic acid autothermal reforming, characterized in that: The catalyst is composed of 15.0% nickel oxide, 41.0% calcium oxide and 44.0% silicon oxide in terms of oxide weight percentage.